Tinjauan Proses Perencanaan Heritage Trails Sebagai Produk Pariwisata dalam RIPPDA Kota Bandung - Teguh Amor Patria (Binus Business Review, 2013)
Despite the fact that Bandung boasts a large number of heritage buildings as tourism potentials which become one of priorities in Rencana Induk Pengembangan Pariwisata Daerah (RIPPDA) Kota Bandung 2007-2016 (municipal tourism development plans), such plan is assumed as less detailed and comprehensive. It also emphasizes only on supply and spatial aspect. This paper reviewed the planning process of heritage trails as tourism product in the tourism development plan. A comparative study between actual and ideal condition was conducted and was presented in descriptive way. It consists of introduction, theoretical background relating to tourism product planning process and heritage tourism, research methodology, actual conditions of heritage trails development in Bandung, critical review of heritage trails in Bandung, and conclusion andrecommendation. Such findings reveal the actual condition of heritage trails development as a growing tourism product in Bandung today, which lacks details, depth, and comprehensiveness, data from the past, and review from supply side in order to plan for a better heritage tourism activity.